Increasing Inequality in Long-Term Earnings: A Tale of Educational Upgrading and Changing Employment Patterns - Matthias Seckler (Review of Income and Wealth, 2021)
This paper provides a detailed decomposition analysis of rising long-term earnings inequality among West German men born between the years 1955 and 1974 based on high-quality administrative data. Educational upgrading is identified as a leading factor behind increasing inequality in the upper part of the long-term earnings distribution. The study also reveals a substantial shift from full- to part-time employment and shows this to be an important factor in explaining rising inequality in the lower part. This effect seems to be quantitatively more important than the increasing incidence of non-employment for the studied cohorts. Overall, increasing inequality in long-term earnings can primarily be attributed to an increasing inequality in average yearly earnings during times of employment as opposed to changes in the total years of employment. The analysis also reveals similarities with the development in the US by documenting a stagnation in long-term earnings among the cohorts studied.
Keywords: 330; income inequality; long-term earnings inequality; RIF decomposition